Study on Corrosion Characterization and Mechanism of the Monitoring Tubing under Air-Foam Flooding Injection Well - NING Chuang, ZHANG Liwei, TONG Zhangbing, JING Zhengzheng, YIN Zhifu (Cailiao Baohu)
Through long-term corrosion monitoring of the air-foam flooding injection well string on site， the corrosion characteristics of the inner and outer walls of J55 tubing at the upper and lower well sections in the air-foam flooding test area injection well environment were studied.The morphologies of the corrosion products were characterized by SEM and 3D confocal microscopy， and the compositions of the corrosion products were analyzed by energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD) analysis.Furthermore， the corrosion mechanism was explored and discussed.The results showed that J55 oil pipe had severe overall corrosion and varying degrees of localized corrosion， with more severe corrosion in the downhole section.The corrosion products on the inner and outer surfaces of different sections of the tubing were different， mainly including Fe0.925O，FeSx，Fe3O4 and FeO(OH).The structure of carbon steel tubing might form cracks and be transgranular micro-cracking during the service of air-foam flooding.